C5a and mammary cancers. - Mohd Noor, Mohd Hezmee (2013)
Mammary cancers are among the most common neoplastic conditions in dogs, and there is evidence that inflammation plays a role in the development of some cancer types in dogs. The compiement system is a major participant in the inflammatory process and the compiement activation component, C5a, is a potent infiammatory peptide. Complement C5a is a pro-inflammatory polypeptide produced during activation of the complement cascade in response to foreign antigens or tissue damage secondary to physical or chemical injury. C5a, via activation of it specific receptor (the C5a receptor) is a major inflammatory mediator contributing to a number of diseases, such osteoarthritis, sepsis and kidney disease. The inflammatory process is integral to many forms of neoplasia and anti-inflammatory therapy is frequently used as an adjunctive treatment for various forms of neoplasia. There is increasing evidence that modulation of complement mediators may be useful to treat a range of diseases where inflammation piays some role This paper will describe some of links between C5 a and mammary neopiasia in the dog, potentially leading to novel therapeutic approaches.